2014
DOI: 10.1186/1471-2229-14-176
|View full text |Cite
|
Sign up to set email alerts
|

Ragweed (Ambrosia artemisiifolia) pollen allergenicity: SuperSAGE transcriptomic analysis upon elevated CO2 and drought stress

Abstract: BackgroundPollen of common ragweed (Ambrosia artemisiifolia) is a main cause of allergic diseases in Northern America. The weed has recently become spreading as a neophyte in Europe, while climate change may also affect the growth of the plant and additionally may also influence pollen allergenicity. To gain better insight in the molecular mechanisms in the development of ragweed pollen and its allergenic proteins under global change scenarios, we generated SuperSAGE libraries to identify differentially expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 99 publications
(101 reference statements)
5
62
0
4
Order By: Relevance
“…A recent study of Timothy grass (Phleum pratense), commonly found across Europe and a frequent cause of seasonal allergies, found that exposure to elevated concentrations of carbon dioxide increased the amount of pollen produced by each flower by approximately 50% [195]. Furthermore, studies of Ragweed (Ambrosia artemisiifolia) suggest that both recent and projected increases in atmospheric carbon dioxide concentration may increase the amount of allergenic pollen produced [196,197]. …”
Section: Allergic Diseasesmentioning
confidence: 99%
“…A recent study of Timothy grass (Phleum pratense), commonly found across Europe and a frequent cause of seasonal allergies, found that exposure to elevated concentrations of carbon dioxide increased the amount of pollen produced by each flower by approximately 50% [195]. Furthermore, studies of Ragweed (Ambrosia artemisiifolia) suggest that both recent and projected increases in atmospheric carbon dioxide concentration may increase the amount of allergenic pollen produced [196,197]. …”
Section: Allergic Diseasesmentioning
confidence: 99%
“…Changes in individual phenolic metabolites have also been reported in A. artemisiifolia pollen upon CO 2 and/or drought stress [43], whereas no changes were observed upon ozone fumigation [14]. The pollen of several other plants species that were sampled from polluted and less-polluted areas showed an increased amount of individual flavonoids [44] [45].…”
Section: Secondary Metabolitesmentioning
confidence: 98%
“…The expression of Amb a 1.01, 1.02, and 1.03 isoallergens could be upregulated under certain environmental situations, such as elevated CO 2 or drought stress, which has been shown in greenhouse experiments [38]. Also, environmental factors such as temperature, humidity, and light had a significant influence on Amb a 1 content [32].…”
Section: Major Ragweed Pollen Allergensmentioning
confidence: 99%
“…Such enzymes are important for pollen growth by degrading pectines [38]. More than 90% of ragweed-allergic patients are sensitized to this major allergen [39].…”
Section: Major Ragweed Pollen Allergensmentioning
confidence: 99%